Wacana Modernisasi dalam Tantangan Peradaban, Peran Perempuan sebagai Tonggak Sejarah Arab Saudi - Rosida, Anis (PALITA, 2018)
New hope is being harvested in the Middle East especially the region of Saudi Arabia, the axis of religious civilization, the history and the crossroad of East and West. A taboo region of the term Modern or even reject the extremes of change. At the moment, since the vision of 2030 is proclaimed as the goal of the absolute state it becomes softened. The Saudi Arabian government is trying to divert its attention so far from oil to a more profitable sector. This process will take a lot of effort in terms of political, religious, cultural, social and economic of course. In this study we can ask âhow the concept of modernization would be brought by Saudi Arabia and its scope, how are these challenges of change occurring and especially in the context of women as milestone to change?,this research take a field study with data sources of factual issues of social media such as newspapers and research results that using data analysis methods about theory of feminism and these results proved that this modernization effort is continuing in this region to attract the negative issues that have so far been the label of the ultra-conservative region and certainly to maintain that power. The most effective thing is to use the issue of women and gender as a milestone until modernizations discourse could be realized.